Effects of Processing Methods on the Chemical Properties of Sprouting Leaf (Bryophyllum Pinnatum) - EC, Omah; CE, Ugwu; BC, Nweze; NP, Akah; DC, Ofoegbu (Journal of Food Technology Research, 2022)
This study was carried out to determine the effects of processing methods on the chemical properties of sprouting leaf (Bryophyllum pinnatum). Fresh leaves of B. pinnatum “Oda opue” were collected, destalked, sorted, washed and drained. The prepared samples were divided into four portions. Three portions were processed by sun drying (14hrs), shade drying (7days) and blanching (90oC for 2mins), the fresh leaves that were neither dried nor blanched served as control. The sun-dried leaf (DL), shade dried leaf (SD), blanched leaf (BL) and the fresh leaf (FL) where analyzed for proximate, vitamin, mineral and phytochemical compositions. The proximate composition ranged as follows; moisture content (8.94 to 89.57%), protein (4.50 to 22.0%), ash (0.81 to 13.81%), fibre (0.84 to 6.86%), fat (0.21 to 2.06%), and carbohydrate (3.52 to 48.57%). The vitamin A content which ranged from 1.40 to 3.92 mg/100g was highest in shade dried leave. Vitamin B1 and C ranged from 210.00 to 295.40 mg/100 g and 18.25 to 27.60 mg/100g, respectively with the shade dried leaves having the highest value. The mineral composition; calcium, magnesium, zinc and iron were highest in shade dried leaf sample and was significantly (p < 0.05) different from fresh, sun dry, and blanched leaves samples. The phytochemical composition ranged from 0.17 to 0.44, 0.60 to 0.85% for saponin and alkaloid, 0.34 to 1.05, 0.17 to 0.58, 0.29 to 0.54 mg/100g and 0.32 to 0.70% for oxalate, phytate, tannin and flavonoid, respectively. The shade dried leaves was found to have higher nutritional composition.